2013
DOI: 10.5301/hipint.5000051
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Abnormal Gait Parameters Due to Increased Femoral Anteversion from other Effects in Cerebral Palsy

Abstract: The effects of increased femoral anteversion (IFA) on gait pattern have a complex relationship with other orthopaedic and neurological abnormalities of cerebral palsy (CP). The aim of this study was to differentiate the effects of IFA from other factors in CP. The four groups in this study included: 15 typically developing children (Group: TDC) (age: 9.7 ± 0.5); 14 TDC with IFA (7.5 ± 1.7) (Group: TDC-IFA); 8 CP participants with IFA (age: 6.3 ± 1.7) (Group: CP IFA); and 10 CP participants with nearly normal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Increased FA refers to a structural deformity that could affect the adjustment of foot progression angle [8], and recent studies have reported that it is a cause of gait abnormalities and lower extremity deformities [9]. Biomechanically, increased FA is thought to place the hip abductor muscles at a biomechanical disadvantage during ambulation by decreasing the functional lever arm relative to the hip joint center during the stance phase [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased FA refers to a structural deformity that could affect the adjustment of foot progression angle [8], and recent studies have reported that it is a cause of gait abnormalities and lower extremity deformities [9]. Biomechanically, increased FA is thought to place the hip abductor muscles at a biomechanical disadvantage during ambulation by decreasing the functional lever arm relative to the hip joint center during the stance phase [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even though there have been several studies focused on the importance of postural control and balance in children with CP, the relationship between FA angle, knee angle and balance is still a question. It was reported that the effect of IFA on gait pattern have a complex relationship with other orthopedic and neurological abnormalities of cerebral palsy [9]. Gait pattern of spastic diplegic CP had been studied by Lin et al, who showed that gait is altered based on the characteristics of the knee joint [13].…”
Section: Introductionmentioning
confidence: 99%
“…12 Such femoral malrotation can lead to an internally rotated gait and increased anterior pelvic tilt; it also causes bony lever arm dysfunction, commonly resulting in a reduction of the internal hip abduction moment. [13][14][15] External tibial torsion can further interfere with the child's ambulation by reducing the knee extension moment. Femoral and/or tibial derotation osteotomies can improve gait by correcting the bony lever arms.…”
mentioning
confidence: 99%
“…Gait analysis also provides further information about pelvic rotation in the transverse plane, and this information can help the surgeon to interpret transverse plane abnormalities [ 11 ]. Akalan et al studied the gait parameters of CP children with increased FA and compared these with those of children with increased FA who were developing normally [ 34 ]. These authors noted that the effects of increased FA differ between a child with CP and a normal child.…”
Section: Discussionmentioning
confidence: 99%